Analisis Tindak Tutur Direktif Ustaz Adi Hidayat dalam Ceramah Kajian Islam pada Kanal YoTube Adi Hidayat Official bertema Keimanan dan Ketakwaan - Silvia Eka Hariyanti; Fijri Astami Febrianti; Ida Milantika; Alexa Ayu Qurrotul Aini; Iqlima Atqiya’ul Aulia; Asep Purwo Yudi Utomo; Isnarto Isnarto; Khairana Salsabila Mumtaz; Khofifah Indah Baitul Jannah (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This study aims to describe the forms and meanings of directive speech acts used by Ustaz Adi Hidayat in his sermon, titled “Faith and Piety,” on the YouTube channel Adi Hidayat Official. The research employs a pragmatic approach with a descriptive qualitative method. Data were obtained through observation and note-taking techniques from three sermon videos, which were analyzed based on the theory of directive speech acts. The study’s results identified 25 directive utterances, comprising six types: challenges (2 utterances), commands (10 utterances), offers (3 utterances), suggestions (6 utterances), requests (2 utterances), and orders (2 utterances). Each type of directive speech act serves a distinct communicative function; however, in general, these utterances aim to influence the audience to act in accordance with Islamic teachings. Ustaz Adi Hidayat employs polite, logical, and persuasive language in his sermons, ensuring that the religious messages are conveyed effectively. This study contributes to the development of pragmatic studies, particularly in understanding language use within the context of Islamic preaching.